Populist Communication During the Covid-19 Pandemic: the Case of Brazi’s President Bolsonaro - Burni, Aline; Tamaki, Eduardo (PARTECIPAZIONE E CONFLITTO, 2021)
Brazil has been one of the hardest hit countries by the Covid-19 pandemic. Far-right populist president Bolsonaro promoted social polarisation and politicised the crisis, while neglecting the seriousness of the health emergency. Despite the consequences of the lack of response by the federal government to contain the high infection rates, Bolsonaro’s approval ratings remained stable and slightly increased during the outbreak. Against this background, this article turns to the question on how populist politicians in government have used communication to frame the Covid-19 pandemic and navigate the crisis. Looking at the case of Brazil, we ask: how was the Covid-19 pandemic framed or used by a populist leader like Bolsonaro? How did he communicate the pandemic in his social media speeches? By mobilising literature on populism from both the ideational and discursive perspective, we formulated a rubric and analysed Bolsonaro’s speeches on social media according to a "populist-crisis" approach, using the holistic grading method. Our findings suggest that, aligned with the literature, populists like Bolsonaro use crises to advance some strategies that can help them maintain support: the creation and blaming of enemies, an alleged proximity to "the people", and the projection of a paradoxical image of "exceptionality" and "ordinariness" of the populist leader.